Molecular analysis for halal verification: screening porcine DNA in charms cosmetic skincare products - Nursyuhada Othman; Hidayah Haris; Nur Hartini Sariyati; Farah Farhana Ramli; Norhayati Muhammad; Mohd Zul Hilmi Mayzan; Muhammad Suhaimi Sulong; Muhammad Abdul Latiff Abu Bakar (Journal of Halal Product and Research)
The growing Muslim population around the world has led to an increase in demand for Halal products such as cosmetic. Previously, the cosmetics business was dominated by non-halal cosmetic enterprises, as many products contained pig-derived substances, which are forbidden in Islam. In 2012, Charms Skincare Cosmetics, a Malaysian cosmetic brand, was established with a focus on producing Halal-certified products. Thus, the aim of the study is to demonstrate that the seven products from the brand are free from porcine DNA, following halal verification. All the cosmetic products were isolated using the Agilent Porcine Detection Kit, and the amplification was done by the real-time polymerase chain reaction (RT-PCR) method targeting porcine-specific DNA sequences from the Cytochrome b region. The result showed no amplification of the Cytb gene in gel visualization and was supported by the absence of porcine DNA using RT-PCR from all seven Charms cosmetic products, representing the absence of any pig derivative substances. These findings indicate that the products comply with Islamic requirements, and the PCR method proves to be a sensitive and reliable approach for the detection of porcine DNA in halal authentication processes.